Case Report: Need for Caution in the Diagnosis of GFAP Astrocytopathy—A Case of GFAP Astrocytopathy Coexistent With Primary Central Nervous System Lymphoma - Fang, Jia; Tong, Zhongyi; Lu, Wei (Frontiers in Neurology, 2022)
We reported a case of primary central nervous system lymphoma (PCNSL) coexistent with glial fibrillary acidic protein (GFAP) astrocytopathy, and discussed the problems needing attention in the diagnosis and differential diagnosis of GFAP astrocytopathy. Our patient was a 51-year-old female who presented with somnolence for a month, and memory declination for 10 days. Brain magnetic resonance imaging (MRI) demonstrated multiple abnormal enhancement lesions in bilateral basal ganglia and around the third ventricle, as well as transient T2-weighted hyper-intensity lesions at the splenium of the corpus callosum during the course of the disease. The cerebrospinal fluid (CSF) was positive for anti-GFAP antibodies by antigen-transfected HEK293 cell-based assay (indirect immunofluorescence assay). She was initially diagnosed with autoimmune GFAP astrocytopathy. After treatment with corticosteroids for about 2 months, she displayed poor response and even worsened clinical manifestations when the dose of prednisone reduced to 45 mg. Stereotactic brain biopsy was adopted and the diagnosis of large B-cell lymphoma, non-germinal center type was established on pathological examination. The results of brain biopsy also showed perivascular inflammation and CD8+ T cell infiltration, which also accorded with GFAP astrocytopathy. After chemotherapy with rituximab and methotrexate, the patient showed clinical and radiological improvement significantly. Our findings suggest that positivity of GFAP antibody calls for cautious interpretation. Cancer screening appropriate for age, sex, and risk factors is recommended for GFAP antibody-positive patients, especially for patients with atypical clinical and radiologic manifestations.